(3HMGQ GdYdhes - (3GdgGTej, CHh YHO Gddg, GdUGOb, fSH Edi(B: (3LYaQ GdUGOb, LYaQ Hf eMeO GdHGbQ Hf Ydjs ((3eMeO MSfs)
(3ChdgG (B:s
(3ChdgG(B: ((3GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH hde jLYd dg YhLG(B...) (3aCbhd(B: (3bO acQJ aj faSj hfXQJ Edi HYOs
(3BNQgG (B:s
(3BNQgG(B: (3aOYi GdJSYI GdHGbjI hSGFQ (B.. (3hGdYOe Ydi YHGOg GdPjf GUWai hGdSdGe Ydi ef GJHY GdgOi HaVdc jG PG GdaVd GdYXje Efg (B.. (3LhGO cQjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 126s
(3GdPQjYI, L (B3: 16 - 17s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds